RelicNet: highly reliable wireless sensor system for microclimate monitoring in wildland cultural heritage sites - XIA Ming1; DONG Ya-bo1; LU Dong-ming1; XUE Ping2 (Tongxin xuebao)
RelicNet, highly reliable wireless sensor system for microclimate monitoring in wildland cultural heritage sites was proposed. RelicNet organized the whole system as a multi-tiered delay-tolerant network （DTN）, and provided a cross-tier data reliability maintenance framework to ensure the reliability of each step of data delivery. The currently de- ployed system consists of 241 sensors covering 57 typical caves of the Mogao Grottoes, a well-known wildland cul- tural heritage site in the Gobi desert. The microclimate change patterns in caves were analyzed using the data col- lected by the system, and the reliability and long lifetime of the system were verified through network and battery performance evaluations.